HARMONISING TECHNOLOGY AND TRADITION: DEVELOPING AN AI-BASED EARLY CHILDHOOD EDUCATION LEARNING MODEL ROOTED IN LOCAL VALUES - Aslan Aslan; Dayan Abdurrahman (Indonesian Journal of Education (INJOE), 2026)
Background: Early Childhood Education (PAUD) forms the foundation for the character development and intellectual growth of future generations. In the era of digital transformation, artificial intelligence (AI) offers significant opportunities to enhance the quality of learning, yet it also poses risks of cultural homogenisation and the loss of local identity. In Indonesia, the diversity of local wisdom represents an asset that has not yet been systematically integrated into educational technology innovations. This study aims to develop and test an ECE learning model that harmonises artificial intelligence technology with the values of Indonesia’s local wisdom, as well as to analyse its impact on children’s development and its relevance to the global context. The study employs a mixed-methods design with an exploratory and descriptive approach. Quantitative data were collected via a survey of 320 early childhood educators across 8 provinces, whilst qualitative data were obtained through in-depth interviews with 45 informants (educators, cultural experts and technology developers) as well as observations at 16 early childhood education institutions. Data analysis was conducted using descriptive and inferential statistics, as well as thematic analysis. It was found that only 22.5 per cent of early childhood education institutions utilised digital content based on local culture, whilst 78.1 per cent expressed an urgent need for materials relevant to the children’s environment. The model developed was shown to increase children’s interest in learning by 34.2 per cent and their understanding of cultural values by 41.7 per cent following a six-month implementation period. This AI-based learning model, grounded in local wisdom, effectively addresses local challenges and offers solutions for other countries facing similar dilemmas. This innovation is novel in that it integrates the principles of knowledge equity and cultural sustainability into the 21st-century education system.